Numerical investigation of turning diffuser performance: validation and verification - Nordin, Normayati (2014)

(untitled)
This paper aims to validate the numerical method used to intensively study the performance of turning diffuser. A 90o turning diffuser of area ratio, AR = 2.16 operated at inflow Reynolds numbers, Rein = 5.786 x 104 and 1.775 x 105 was considered. Hybrid grid with a large number of grid points located at the inner and outer walls was generated. The applicability of k-  turbulence models, i.e. standard k-  (ske), renormalization group k-  (rngke) and realizable k-  (rke) by means of adopting appropriate near wall treatments to simulate the actual cases, was assessed. The enhanced wall treatment adopted ske appeared as the best validated model, producing minimal deviation with comparable flow structures to the actual cases.